Social context modulates scale-free movements in a social insect. (7th June 2022) - Castiblanco, Julieth; Cristaldo, Paulo F.; Paiva, Leticia R.; DeSouza, Og
Highlights: We inspected social context as a proximate driver of intermittent movement in animals. Confined termites showed Lévy-like movement not connected to foraging behaviours. Their pattern of movement depended on the social context (nestmates' density & castes). Higher densities of nestmates favoured Lévy-like movement of the focal termite. Higher proportions of workers relative to soldiers also favoured Lévy-like movement. Abstract: Most animals move intermittently, pausing or slowing down for short moments and short moves, and darting away towards a new location where to hover again. This pattern occurs at a range of spatial and temporal scales (thence, resembling 'scale-free'), from the quick inspection of local areas to the sum of all movements performed from birth to death. While this pattern has been extensively described, its proximate drivers remain open to debate. A current hypothesis states that underlying proximate generative mechanisms of intermittent movement of animals are linked to external stimuli, e.g., interactions with the abiotic environment, resources, and other individuals. Here we investigated a prediction from this hypothesis, using termites as a biological model. We verified whether the social background in which a termite is inserted will modify the parameters of its intermittent scale-free spatial displacement. This relates to the hypothesis because it inspects how do external stimuli coming from intraspecifics can affect this type of movement. We tracked the trajectories of a focal termite confined along its nestmates in experimental clueless arenas, every 0.5 s along about six hours. Arenas varied in group size and comprised 22 distinct caste compositions, yielding 75 trackings ( > 400 h) and more than two million Cartesian coordinates. Most of these trajectories (96% or 72/75) were classified as intermittent scale free (Lévy-like), indicating prevalence of this type of movement over non-Lévy-like ones ( P = 1.62 × 10 - 15 ). Moreover, intermittent scale-free movements performed by the focal termite (i) did arise outside the foraging-searching framework, and (ii) were modified by the social context while remaining within the limits of Lévy-walk realms. That is, some limits seem to exist along with the necessary plasticity to provide room for natural selection. Moreover, by arising outside the foraging framework, Lévy-like movements are shown to have broader relevance. Studies on processes that depend on social context and movement ( e.g., collective behaviour, the spread of diseases) may, hence, profit from such concepts.